Experimental Verification of High-Temperature Resistance and High Resolution of Inductive Tip Clearance Measurement System - Ziyu Zhao; Lingqiang Zhao; Yaguo Lyu; Zhenxia Liu (Sensors)
An inductive clearance measurement sensor has advantages of good anti-interference, fast response speed, and high sensitivity, and it has obvious technical potential in aeroengine turbine tip clearance measurement. In this paper, a rotor dynamic tip clearance measurement experiment system was designed based on a high-resolution inductive measurement system. The high temperature calibration experiment, performance verification experiment, and dynamic clearance measurement experiment under varying operating conditions were used to verify the high-temperature dynamic measurement performance of the measurement system. The resolution was used as the evaluation parameter of measurement performance. The experimental result shows the system has good resolution and dynamic response at 1000 °C, and the dynamic resolution reaches 10 μm in the 3 mm measuring range. The varying condition experiment results show that the blade deformation caused by the speed change of 1000–3000 r/min and the temperature change of 600–1000 °C can be resolved, and the resolution reaches about 10 μm. The research results verify that the inductance clearance measurement system has the characteristics of high temperature resistance and high resolution, and the technical specifications of clearance detection meet the basic requirements of dynamic clearance measurement of turbine tips, which provides an effective detection method for aeroengine health monitoring.